Evaluation of important mineral nutrients and vitamins in polyherbal medicines used for the treatment of tuberculosis in the Eastern Cape Province, South Africa - Elizabeth Bosede Famewo; Anna Maria Clarke; Anthony Jide Afolayan (International Journal of Phytomedicine, 2018)
Polyherbal medicines are widely used for the treatment of various diseases in the developing countries. In order to validate their ability in boosting the immune system of tuberculosis patients, the mineral nutrients and vitamins present were determined. Their nutritive properties were analysed using an inductively coupled plasma optical emission spectrometer, while the vitamins were determined using standardized methods. The polyherbal preparations were found to be rich in mineral nutrients and vitamins. Calcium was the highest mineral nutrient detected, while the lowest nutrient was phosphorus. Quantitatively, calcium and magnesium contents in the remedies ranged from 973.30 to 6503.30 mg/100g and 80.00 to 406.00 mg/100g respectively. The amount of phosphorus and potassium was between 20.00 and 263.30 mg/100g; 160.00 and 2050.00 mg/100g respectively. Micro nutrients such as iron, manganese, zinc, aluminium and copper were also detected. Iron was the highest nutrient in the majority of the polyherbal preparations while the lowest value was recorded for copper. However, vitamin C was absent in the herbal preparations while vitamin A and E were detected. These findings indicate that these polyherbal formulations contain the essential mineral nutrients and vitamins that could probably be boosting the immune system of tuberculosis patients.